Evaluation of Pattern of Lipid Profile of Subjects With Different Abo Groups in Madonna University Elele Rivers State Nigeria - Nnodim Johnkennedy; Francis Ukpevie Goody (Journal La Medihealtico, 2022)
This study looked into how the lipid profiles of people with various ABO blood groups varied. 50 healthy patients with varied ABO blood groups were studied, including 12 A, 12 B, and 10 AB and 16 O blood groups, all of whom appeared to be in good condition and appeared to be asymptomatic. Men and women between the ages of 15 and 25 years old provided informed consent and met the inclusion criteria. Colorimetric measurements of serum lipid profiles were performed on blood samples collected in accordance with routine operating protocols. The results were expressed as MeanSD, and the means of the groups were compared using an analysis of variance (ANOVA). Values with p0.05 were considered significant, whereas those with p>0.05 were not. Averages for TCH and TG in group A were 4.21 and 0.99 millimol/L, respectively. HDL and LDL were both 1.71 and 0.07 millimol/L higher in this group. TCH was 4.2 0.48 mmol/L, TG was 0.74 0.35 mmol/L, HDL was 1.6 0.62 mmol/L, and LDL was 2.26 0.45 mmol/L on average in group B. TCH (4.3 0.88 mmol/L), TG (0.96 0.49 mmol/L), HDL (1.8 0.52 mmol/L) and LDL (1.94 0.81 mmol/L) were found in the group AB patients. When the TCH, TG, HDL, and LDL mean values of the various ABO blood groups were examined, there was no significant difference (p>0.05). This study's findings suggest that blood type has no effect on the serum lipid profile of healthy persons.